Enhancing Supercapacitor Simulation Accuracy Through a Novel Hybrid Modeling Approach - Diana Lemian; Florin Ioan Bode; Ciprian Lapusan (Applied Sciences)
In the last 2 decades, supercapacitors have become an important component in the hybrid energy-storage system, in combination with batteries. The resulting system offers higher performance in comparison to classic energy storage systems due to the complementary advantages offered by the two components. Accurate modeling of supercapacitors and batteries is an important step in the development process of hybrid energy storage systems. The presence of proper models has a direct impact on the optimal design of the energy management strategies and in enhancing the lifespan and performance of the system. In this paper, a new approach for modeling methods for supercapacitors, named Hybrid Modeling Approach for Supercapacitors (HyMASC), is proposed. The proposed method uses an equivalent RC circuit model to capture the dynamics of the supercapacitor and introduces a hybrid method to optimally calculate the model parameters. The validation of HyMASC is done using two supercapacitors with different capacitances. The obtained numerical models were simulated in Matlab for different scenarios, and their results and performance were compared with other methods from the literature. It was observed that the proposed method offers good results with better performance, thereby contributing to the advancement in the field of supercapacitor modeling techniques.